Cerebellar connections: hypothalamus - ONAT, FİLİZ (TAYLOR & FRANCIS LTD, 2003)
Morphological studies have described reciprocal cerebello-hypothalamic projections in various species. These connections provide evidence for the key role of the cerebellum and hypothalamus in physiological regulatory processes such as autonomic and endocrine homeostasis. Our recent study using horseradish peroxidase (HRP) retrograde axonal transport technique showed cerebellar connections with the posterior and the dorsomedial hypothalamic nuclei. Further, we have demonstrated regional differences of the connections of the dorsomedial hypothalamic nucleus in rat. The results of HRP labelling showed that afferent pathways originating from the anterior and posterior parts of dorsomedial hypothalamic nucleus indicate a number of differences in the projections. The posterior part of the dorsomedial hypothalamic nucleus and the posterior hypothalamic nucleus receives direct distinct projections from the cerebellum, whereas the anterior part of the dorsomedial hypothalamic nucleus does not. Moreover, the posterior part of the dorsomedial nucleus of the hypothalamus when compared to the posterior hypothalamic nucleus has more intense connections with the cerebellum. These observations bring a new perspective on the question of how the cerebellum is involved in the regulation visceromotor functions.
Keywords: hypothalamus; connections; cerebellum; rat; PRIMARY MOTOR CORTEX; HORSERADISH-PEROXIDASE; CARDIOVASCULAR-RESPONSES; FUNCTIONAL CONNECTIVITY; SUPERIOR COLLICULUS; FASTIGIAL NUCLEUS; RETICULAR NUCLEUS; CONSCIOUS RATS; RHESUS-MONKEY; BASAL GANGLIA